Pengujian Black Box pada Aplikasi Sistem Pemesanan Berbasis Web pada Toko Buku Setia Kawan Menggunakan teknik boundary value analysis - achmad ferrysqo irawan; ryan setiawan; yasinta dewi; Aries Saifudin (Teknik Informatika Universitas Pamulang, 2022)
The Setia Kawan Bookstore application is an application that is designed and created to make it easier for buyers to view any information about the products available at the Setia Kawan Bookstore online, but cannot be used in general because there are still problems so it is necessary to do testing in order to minimize a failure and also an error that can cause feelings of disappointment in carrying out the bookstore sales activities. The system application that has been designed and created must be tested first, the Setia Kawan Bookstore testing application uses the boundary value analysis method. Application testing that has been made must go through testing so that the application has good quality. A test is said to be good if the test finds an error that is difficult to find. Among the many black box testing methods, in this case the examiner uses the boundary value analysis method. The method tested the number of appropriate maximum and minimum limits and found valid results. The first process in testing this application is to provide activities to be tested, create test designs, and select test materials. And determine with certainty that the maximum and minimum are in accordance with the structure of the data base, and make documentation based on the test results obtained and draw a conclusion that the application can be used properly. The Setia Kawan Bookstore application can be used when the test has been completed and is said to have been successful if all errors have been resolved before being used by the buyer.